Implementasi Tujuan Pembelajaran Pada Kandidat Security Melalui Kawasan Afektif Berbasis Hukum Di PT Javas Anugrah Perkasa - Selviani, Diah; Wahyudi , Jusuf; Rachayu, Imma; Maryani , Desy; Lutfhia , Izza (Jurnal Kewirausahaan dan Bisnis, 2021)
Based on the Community Service activities that were carried out on July 9 2021, we received a good response from the community as seen from their remarks welcoming the collaborative PKM Team from FKIP Computer Education Study Program, Faculty of Law and Faculty of Computer Science, University of Dehasen Bengkulu. The implementation of this community service activity is a form of activity that supports the PT Javas Anugrah Perkasa Bengkulu Security Guard Candidate program to improve ability to understand law-based affective areas and be motivated to understand increasingly advanced technology at this time.